The Intraoperative Use of a Portable Cone-Beam Computed Tomography System for the Diagnosis of Intraperitoneal Bladder Perforation - Ankur Choksi; Benjamin Press; Cayce Nawaf; Shannon Longyear; Marc Ferrante; Thomas V. Martin (Case Reports in Urology)
Background. Intraoperative imaging for endourologic procedures is generally limited to single-plane fluoroscopic X-ray. The O-arm™ is a mobile cone-bean CT scanner that may have applications in urologic surgeries. Case Presentation. We present a case of an 85-year-old male with radiation cystitis and recurrent gross hematuria who was identified to have a bladder perforation on cystoscopy during emergent clot evacuation. Single-view fluoroscopic evaluation was inconclusive as to whether an intraperitoneal bladder perforation occurred. A portable cone-beam CT scan was used to acquire a 3-D CT cystogram, which demonstrated intraperitoneal contrast extravasation, confirming the diagnosis of an intraperitoneal bladder perforation. Conclusion. We report the first use of a portable cone-beam CT scanner to perform an intraoperative CT cystogram to diagnose an intraperitoneal bladder perforation and guide surgical management.